The Effect of Investment, Per Capita Income, and Population on Economic Growth of 34 Provinces in Indonesia - Aprelia, Rizky Wahyuning Putri; Arisetyawan, Kukuh (Arbain Publishing, 2025)
Economic growth seen from GDP value will always be an important topic in projecting a country's progress, the many factors that drive economic growth in a country need to be studied further for the real impact that will occur on the economic growth of a region. This study examines the influence of several factors driving economic growth: investment projected by Foreign Direct Investment and Domestic Investment, per capita income, and population. This study analyzes panel data obtained from 34 provinces in Indonesia in the period 2019-2023 and found a positive influence on the level of investment and per capita income on economic growth, but the analysis carried out showed that the total population hurts the level of economic growth in the area studied.